2013
DOI: 10.1016/j.cedpsych.2013.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Teaching planning or sentence-combining strategies: Effective SRSD interventions at different levels of written composition

Abstract: This study tested the effectiveness of two strategy-focused interventions aimed at promoting fifth and sixth graders' opinion essay writing. Over 12 weekly 90-min lessons, two groups of 48 and 39 students received, respectively, planning and sentence-combining instruction, which followed the Self-Regulated Strategy Development (SRSD) model. These intervention groups were compared with a practice control group of 39 students receiving standard writing instruction. The following main findings were noteworthy: (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
47
0
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 57 publications
10
47
0
14
Order By: Relevance
“…This result is consistent with intervention research showing that promoting these two skills is among the best effective ways to boost school-aged children writing performance (Graham & Perin, 2007). Indeed, a recent study directly comparing the effects of planning and translating interventions in Grades 5-6 (Limpo & Alves, 2013b) showed that both interventions had a strong and positive impact on writing quality. Additionally, the authors reported some transfer effects of planning and translating instruction, respectively, on sentence-and ideation-related aspects of writing.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…This result is consistent with intervention research showing that promoting these two skills is among the best effective ways to boost school-aged children writing performance (Graham & Perin, 2007). Indeed, a recent study directly comparing the effects of planning and translating interventions in Grades 5-6 (Limpo & Alves, 2013b) showed that both interventions had a strong and positive impact on writing quality. Additionally, the authors reported some transfer effects of planning and translating instruction, respectively, on sentence-and ideation-related aspects of writing.…”
Section: Discussionsupporting
confidence: 76%
“…Planning was assessed in a free planning task that students made before writing an opinion essay (Berninger et al, 1996;Limpo & Alves, 2013a;2013b). Translating was measured in the opinion essay written after the planning, together with a sentence-combining exercise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations